Elastic-Plastic Seismic Performance for Jacket Platform Based on Improved Modal Pushover Method - LIU Hongbing; SUN Liping; AI Shangmao; YAN Fasuo; CHEN Guoming (Shanghai Jiaotong Daxue xuebao, 2021)
In connection with the elastic-plastic failure problem of offshore jacket platform subjected to a powerful earthquake, an improved modal pushover method based on performance design is proposed. The elastic-plastic seismic performance and failure modes of the jacket platform are obtained to solve the problem of elastic-plastic performance evaluation of the offshore jacket platform in strong earthquakes. The elastic-plastic seismic responses of the platform in 8-degree seismic fortification and rare intensity are calculated by using different methods, and the differences between these responses are compared. Besides, the influences of combined modes, mode shape vectors, and uncertainties of seismic are discussed. The results show that the high-order vibration modes and mode shape vectors have a great influence on the elastic-plastic seismic performance of the platform. The first 9 or higher order modes and mode shape vectors should be adopted. The seismic-resistant weak links are located at the top of the platform in 8-degree seismic fortification and rare intensity, which should be paid more attention to. The seismic responses of the platform show significant differences and discreteness in different seismic activities, which have the same peak seismic acceleration. The improved modal pushover method is suggested to be used to evaluate the elastic-plastic seismic performance of jacket platform.